Respons Fisiologis Tanaman Jagung Manis terhadap Aplikasi Herbisida dalam Pengendalian Gulma - Bayyinah, Lafi Naimatul; Purwanto, Purwanto; Syarifah, Risqa Naila Khusna; Pratama, Rama Adi (Universitas Wiralodra, 2024)
Sweet corn is a vegetable that people like. One of the problems in sweet corn cultivation is weeds, because it became competitors for getting nutrients, water, light, and hosts of disease. The usage of herbicides for weed control is widely used by farmers. This research aims to determine the effect of herbicides in weeds controlling on the physiology of sweet corn. The experimental design used is Randomized Block Design with 4 replications. Treatments tested included: no weed control; manual weeding; paraquat; glyphosate; paraquat, atrazine, mesotrione; glyphosate, atrazine, mesotrione; paraquat, atrazine, mesotrione, nicosulfuron; and glyphosate, atrazine, mesotrione, nicosulfuron. The variables observed are herbicide phototoxicity on corn plants, leaf area, leaf area index, net assimilation rate, plant growth rate, leaf chlorophyll content, and plant dry weight. Data were analyzed using ANOVA, if there are significant differences then continued with Duncan Multiple Range Test at 95% confidence level. The results of show that weed controlling using various herbicide active ingredients has effect on the physiology of sweet corn. The best treatment was shown by combination of paraquat, atrazine and mesotrione which shows the highest values ​​at variables leaf area, leaf area index, plant dry weight, leaf chlorophyll content, net assimilation rate and plant growth rate of sweet corn.